Insights of cellular and molecular changes in sugarcane response to oxidative signaling - Lucas Felipe Silva; Kellya F. M. Barreto; Helaine Cristiane Silva; Iara Dantas de Souza; Carlos H. S. G. Meneses; Adriana F. Uchôa; Katia C. Scortecci (BMC Plant Biology)
Abstract Main conclusion Significant changes in the proteome highlight essential metabolic adaptations for development and oxidative signaling induced by the treatment of young sugarcane plants with hydrogen peroxide. These adaptations suggest that hydrogen peroxide acts not only as a stressor but primarily as a signaling molecule, triggering specific metabolic pathways that regulate growth and plant resilience. Abstract Sugarcane is a crucial crop for sugar and ethanol production, often influenced by environmental signals. Hydrogen peroxide (H2O2) is increasingly recognized as an important signaling molecule that regulates plant development and adaptation. In this study, two-month-old sugarcane plants were treated with varying concentrations of H2O2 to investigate how this molecule acts as a signal at the cellular, biochemical, and proteomic levels. Antioxidant enzyme activity exhibited fluctuations, suggesting a dynamic response to oxidative signaling. Lipid peroxidation, observed through TBARs and scanning electron microscopy, highlighted early membrane modifications. Proteomic analysis (ProteomeXchange PXD048142) identified 2,699 proteins, with 155 showing significant expression changes in response to H2O2 signaling. Bioinformatics, including Principal Component Analysis, revealed distinct proteomic profiles in roots and leaves, indicating tissue-specific metabolic reprogramming. Functional annotation through Gene Ontology and KEGG pathway enrichment showed that oxidative signaling led to the repression of photosynthesis-related pathways in leaves, while promoting pathways related to protein processing, glycolysis, and carbon metabolism in roots. Additionally, bioinformatic tools identified proteins involved in amino acid metabolism, the TCA cycle, and carbohydrate metabolism as critical components of sugarcane's adaptive signaling response. The data suggest that sugarcane plants responded to oxidative signals by adjusting their metabolic networks, promoting sustained development and potential pathways for targeted plant breeding.